Bridging the gap: How the National Core Arts Standards forge the divide between the arts and assessment-based learning. Issue 4 (2nd October 2019) - Willerson, Amy
ABSTRACT: This article is a review and thematic analysis of the 2014 National Core Arts Standards (NCAS). Historically, there exists a gap between the arts and assessment-based educational practices. Thematic analysis of the NCAS reveals a policy striving to bridge the gap between the way arts educators envision arts in schools, and the current reality of assessment-based schooling in the United States. This policy could become the foundation for the recognition of the arts as academically rigorous subject matter, capable of existing and thriving in an assessment-oriented world; it remains to be seen as to how and if arts educators will use and adapt NCAS. Is the NCAS merely a symbolic policy or does it have the support behind it to be a material policy that truly creates change in the educational system?